FACULTY ONLINE LEARNING READINESS OF A PRIVATE SECONDARY SCHOOL IN BICOL, PHILIPPINES AMIDST THE NEW NORMAL: BASIS FOR AN EXTENSION PROGRAM - Medalla, Jopet Vincent; Dipad, Mark Anthony; De Vera, Christian Paulo (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The emergence of Corona Virus Disease 2019 pandemic required educational institutions to shift to new instructional paradigm to ensure learning continuity. With the restrictions on mass gathering, online distance learning has emerged as one of the alternative modalities. This descriptive study primarily aimed to assess the faculty readiness of St. Louise de Marillac School of Bulan (SLMSB), Inc., a private secondary school in Sorsogon Province, Bicol Region, The Philippines, in implementing online learning as an alternative instructional mode. Using an adopted survey-questionnaire, twenty (20) faculty members participated in this research. It was found that the faculty members of SLMSB are sufficiently ready on online learning in terms of their technology access, considering the measures being undertaken by the school administration. They are also ready in terms of their technology skills and their attitude towards online learning. However, despite the general result on readiness, analysis of the indicators revealed that they need to be trained in terms of use of online learning management system, and use of tools for developing learning materials. With these results, it is recommended that a capability-building program for faculty members of SLMSB be conducted in order to prepare them in facilitating online learning through an extension program that may be offered by Sorsogon State College – Bulan Campus.